SYNTHESIS OF MAGNETITE CORE CD(II)-IMPRINTED POLYMERS FOR CD(II) ION PRECONCENTRATION - ANANDHYTA (NIM : 10510030) ;Pembimbing Prof. Dr. Muhammad Bachri Amran, DEA , NUNGKY
The presence of heavy metal has been a serious environmental problem. Based on chemical properties and contamination level of that heavy metal, it is possible to occur a negative impact to the ecosystem, neither water ecosystem nor human ecosystem. Many experiments have been focused to an invention of this contaminant analysis and preparation method, such as precipitation, reduction, liquid extraction, ultrafiltration, ion exchange, adsorbtion, etc. The most important problem is, the composition of that heavy metal is only a little amount in contained in nature (μg.L-1 level). Ion imprinted polymers is a sensitive, selective fungsional materials and capable to use as solver for problem described. This preconcentration method is based on solid phase extraction. IIP has an ability to combine with magnetic particle to simplify the solid separation process from sample solution. In this experiment, Cd(II)- imprinted polymers was synthesized using salicylic acid as monomer and formaldehyde as crosslinker, and Cd(II)-4-(2-pyridylazo) resocinol complex in stoichiometric comparison 1:1. Magnetite was synthesized using co-precipitation method. Synthesis this magnetite core polymers was carried out with thermal method, stiring salicylic acid, formaldehyde, Cd(II)- 4-(2-pyridylazo) resocinol complex, and magnetite, heating for 10 hours at 140 Ã‚Â°C using HCl 2 M as catalyst. Resulting polymers was characterized using FTIR to determine formation of polymers and releasing process of Cd(II) ions. Retention properties of Cd(II)-imprinted polymers was characterized by using Batch method. The result showed that the optimum capacity of that polymer for adsorpting Cd(II) was 8,92 mg/g at pH 5 with contact time of 5 minutes. Retention Cd(II) ions followed both types of adsorption isoterm, Langmuir and Freundlich with ΔG value is -16,211 kJ/mol. ΔG value shows that the adsorption process was spontaneous, exotherm, and implied in weak chemical adsorption. Relative selectivity value for Pb(II), Zn(II), and Cu(II) was 1,226 ; 2,206 ; 1,668. The values indicated that magnetite core Cd(II)-imprinted polymers is selective for Cd(II) ions.